PERANCANGAN APLIKASI MOBILE CATALOG MODEL RAMBUT DENGAN MENERAPKAN ALGORITMA CROCHEMORE PERRIN - Sri Hardiyanti (STMIK Budi Darma, 2019)
In modern times, barbershop aka men's shaving places is the main choice of modern men to style their hair. The results showed that the popularity of Barbershop itself is due to the trend of the haircut, the classic hairdo. Classic hairstyle trends are also supported by the media which has a positive impact on popularity, hair fashion as a priority, knowledge about fashion is getting better, pomade trends. In general, customers want to get the best quality of services provided.Changes in customer haircuts or Barbershop customers are usually caused by changing trends or because they want to find new models that are more age-appropriate. The haircut catalog is a book that contains information on various haircut models that are made in the form of pictures and names of haircuts, where the names of haircuts are generally made in English.The problem that can occur in cutting hair is the lack of desires of the customer to the results of the hair stylist cut, it happens because the customer does not understand or do not remember the name of the desired haircut model. Crochemore Perrin's algorithm factored the right pattern so that pattern = right pattern left pattern. The matching phase of this algorithm consists of two parts, first matching the right pattern character from left to right, then matching the left pattern from right to left.Keywords: Barbershop, Android, Catalog, Crochemore Perrin